WEAK OPEN SETS ON SIMPLE EXTENSION IDEAL TOPOLOGICAL SPACE - AL-Omeri, Wadei; Noorani, Mohd. Salmi Md.; AL-Omari, Ahmad (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper we intend to introduce a new class of sets known as e-\(\mathcal{I}\)+-open sets, defined in the light of simple extension topology and ideal topology. This set is investigated and found to be a weaker form of e-\(\mathcal{I}\)-open sets. We have also generalized this concept and studied its properties.